Islamic Education Management in Islamic Boarding Schools: Integration of Ecological Values ​​in the Educational Curriculum - Nurul Latifatul Inayati; Abil Fida Muhammad Qois Al Hadi; Fadhia Ananda; Istanto; Fadhilla Nangroe Anggraini; Rabi’atul’adawiyah Binti Jamaludin (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2025)
Climate change and environmental degradation are global challenges that demand the involvement of the education sector in sustainable development. In Indonesia, pesantren as traditional Islamic educational institutions have a strategic position because they not only transmit religious knowledge, but also shape the social values and practices of the community. Some Islamic boarding schools have developed waste management, renewable energy, and organic farming programs, but these initiatives are still sporadic and rarely systematically studied. This research aims to examine the contribution of pesantren to environmental education and sustainable development, identify practices, challenges, and opportunities that arise, as well as map the latest research trends. The study was conducted with a Systematic Literature Review (SLR) using the PRISMA 2020 framework. Literature searches on Scopus, Web of Science, and Google Scholar (2020–2025) using Boolean strings: TITLE-ABS-KEY (